Beta oscillations in the sensorimotor cortex correlate with disease and remission in benign epilepsy with centrotemporal spikes. Issue 3 (20th February 2019) - Song, Dan Y.; Stoyell, Sally M.; Ross, Erin E.; Ostrowski, Lauren M.; Thorn, Emily L.; Stufflebeam, Steven M.; Morgan, Amy K.; Emerton, Britt C.; Kramer, Mark A.; Chu, Catherine J.
Abstract: Introduction: Benign epilepsy with centrotemporal spikes (BECTS) is a common form of childhood epilepsy with the majority of those afflicted remitting during their early teenage years. Seizures arise from the lower half of the sensorimotor cortex of the brain (e.g. seizure onset zone) and the abnormal epileptiform discharges observed increase during NREM sleep. To date no clinical factors reliably predict disease course, making determination of ongoing seizure risk a significant challenge. Prior work in BECTS have shown abnormalities in beta band (14.9–30 Hz) oscillations during movement and rest. Oscillations in this frequency band are modulated by state of consciousness and thought to reflect intrinsic inhibitory mechanisms. Methods: We used high density EEG and source localization techniques to examine beta band activity in the seizure onset zone (sensorimotor cortex) in a prospective cohort of children with BECTS and healthy controls during sleep. We hypothesized that beta power in the sensorimotor cortex would be different between patients and healthy controls, and that beta abnormalities would improve with resolution of disease in this self‐limited epilepsy syndrome. We further explored the specificity of our findings and correlation with clinical features. Statistical testing was performed using logistic and standard linear regression models. Results: We found that beta band power in the seizure onset zone is different between healthy controls and BECTS patients. We also found that a longer duration of time spent seizure‐free (corresponding to disease remission) correlates with lower beta power in the seizure onset zone. Exploratory spatial analysis suggests this effect is not restricted to the sensorimotor cortex. Exploratory frequency analysis suggests that this phenomenon is also observed in alpha and gamma range activity. We found no relationship between beta power and the presence or rate of epileptiform discharges in the sensorimotor cortex or a test of sensorimotor performance. Conclusion: These results provide evidence that cortical beta power in the seizure onset zone may provide a dynamic physiological biomarker of disease in BECTS. Abstract : Benign epilepsy with centrotemporal spikes (BECTS) is a common, sleep‐activated self‐limited childhood epilepsy with no currently available clinical biomarkers to predict disease remission. Here, we used high density EEG combined with MRI and electrical source imaging techniques to test whether beta power during sleep in the focal seizure onset zone (sensorimotor cortex) predicts disease state and seizure risk. We found that beta power in the seizure onset zone differentiates between BECTS patients and healthy controls and predicts disease remission in children with BECTS.